Analisis Instrumen Pasar Modal Terhadap Pilihan Berinvestasi Masyarakat Generasi Z: Melalui Studi Literatur - Yuke addria Futri; Riski Romadoni; Yolanda Meyni Regina Wardhani; A. Rifki Hidayat; Asyfa Nur Baiti; Muhammad Galih Anugrah Adha (CV. Denasya Smart Publisher, 2025)
Along with the development of technology and digitalization, there has been a change in people's consumption patterns, including generation Z, one of which is in the field of investment. However, generation Z finds it difficult to choose investment instruments due to a lack of understanding of how the capital market works. They also face challenges such as low financial literacy, high risk perception, unstable economic conditions, and the influence of the surrounding environment that raises doubts about starting an investment. This study aims to analyze what instruments can be chosen by generation Z as novice investors, so this study is expected to help generation Z to be able to start investing with the right choice of instruments. This study uses a qualitative descriptive method by collecting various definitions of capital market instruments and their risk levels, as well as related theories from various sources (literature review) such as articles, news, and books to determine the results of the study. The results of the study show that there are five types of capital market instruments, namely stocks, bonds, mutual funds, SBN, and warrants, each of which has different advantages and risks. Based on the analysis, mutual funds are a suitable investment instrument for generation Z as novice investors.